Self-assembled iRGD-R7-LAHP-M nanoparticle induced sufficient singlet oxygen and enhanced tumor penetration immunological therapy. Issue 31 (28th July 2022) - Wang, Yu-e; Zhai, Junqiu; Zheng, Yuxiu; Pan, Jiali; Liu, Xiaojia; Ma, Yan; Guan, Shixia
Abstract : (a) Schematic illustration for the preparation of iRGD-R7-LAHP-M NPs. (b) The prepared NPs penetrated into the deep tumor, and released LAHP and metal ions in acid pH, inducing singlet oxygen-mediated cell death and evoking immunogenic cell death. Abstract : The generation of singlet oxygen ( 1 O2 ) using photodynamic therapy (PDT) is limited by the hypoxia of the tumor microenvironment and the depth of external light penetration because it depends on the precise cooperation between the photosensitizers, oxygen, and light. Herein, we report a self-sufficient 1 O2 nanoreactor with enhanced penetration into deep tumors for cancer therapy. Linoleic acid hydroperoxide (LAHP) is coordinated with transition metal ions (Cu 2+ /Fe 3+ ) to prepare linoleic acid hydroperoxide metal complex nanoparticles (LAHP-M NPs). iRGD combined with R7 decoration endows the nanoparticles with tumor targeting and penetration ability. We show that the polypeptide carries the nanoparticles into deep tumors, and thereafter the nanoparticles are disassembled into LAHP and catalytical metal ions to produce 1 O2 based on the Russell mechanism under the stimulation of acidic pH. The elevated ROS induces necrotic cell death in vitro and in vivo, and further causes immunogenic cell death (ICD). This study demonstrates the effectiveness of exploiting biochemical reactions as a spatial-temporal strategy to overcome the current limitations of photodynamic therapy.